Cold War holidays : American tourism in France - Endy, Christopher (New Cold War history., 2004)
Christopher Endy approaches the Cold War-era relationship between France and the United States from the original perspective of tourism. Focusing on American travel in France after World War II, Cold War Holidays shows how both the U.S. and French governments actively cultivated and shaped leisure travel to advance their foreign policy agendas.